Management of Dushta Vrana with an Ethnomedicine Theepana (Allophylus Cobbe (L.) Raeuch Leaves Choorna (International Journal of Ayurveda and Pharma Research, 2024)
“Ethno” (derived from “ethnic”) is a custom of a particular race or religion and ethnomedicine is a custom of medicine. The discovery of new crude drugs from indigenous reported medicinal plants can be done from ethnomedicinal studies. There is a persistent increasing demand of medicines in the market which makes them costlier. Because of which the use of other substitutes and adulterants is increasing; questioning the efficacy of the actual medicine. Theepana could help to overcome the cost and adulteration of other Vranaropan medicines like Arjun. It is from Sapindaceous family; (soapberry family). Genus is Allophylus. Sanskrit name- Triputa (only according to some viewers. No textual reference available for Triputa as Sanskrit name). Marathi name- Theepana, Thivana, Tipin. Theepana (Allophylus cobbe (L.) Raeuch” leaves Choorna was used as an ethnomedicine in Dushta vrana. The leaves Choorna shows Shothagna (anti-inflammatory), Krimigna (antimicrobial), Vranashodhana and Vrana ropan effects. Dushta vrana (chronic ulcer), manifested in any part of the body, may be caused either by the Doshas or trauma. When caused due to the Doshas, it is called Nija vrana and when caused because of trauma; it is called Aagantuja vrana. According to Madhav Nidan-Vrana having Durgandhit - more Gandha, Vedana, Puyayukta Strava, Chirsthithi and Strava, Varna is known as Dushta Vrana.